2015
DOI: 10.17265/1934-8975/2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Modified Nitrogen-Doped Graphene Electrocatalyst for Oxygen Reduction Reaction in Alkaline Fuel Cells

Abstract: Abstract:We report modified nitrogen-doped graphene (CN) as electrocatalyst for ORR (oxygen reduction reaction) in alkaline medium. CN was synthesized by a novel procedure based on graphite oxide thermally treated with cyanamide suitable for facile N-doping and large-scale production, whereas cyanamide was used as N-precursor. The structure of the material was characterized by TEM (transmission electron microscopy), SEM (scanning electron microscopy), Raman spectroscopy and XPS (X-ray photoelectron spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…While novelties and outstanding properties are regularly praised in numerous studies, the performance examination under real operating fuel cell conditions has so far been rather neglected, since measurements in liquid electrolyte and three-electrode configuration are not sufficient to evaluate the potential of novel electrode concepts. In our previous study, we have already presented that prepared N-graphene demonstrated better catalytic activity towards ORR than nondoped graphene at alkaline conditions [16]. Besides, we have especially demonstrated the selectivity of prepared N-graphene for ORR in presence of glucose and D-gluconic acid in pH-neutral media [17].…”
Section: Introductionmentioning
confidence: 77%
“…While novelties and outstanding properties are regularly praised in numerous studies, the performance examination under real operating fuel cell conditions has so far been rather neglected, since measurements in liquid electrolyte and three-electrode configuration are not sufficient to evaluate the potential of novel electrode concepts. In our previous study, we have already presented that prepared N-graphene demonstrated better catalytic activity towards ORR than nondoped graphene at alkaline conditions [16]. Besides, we have especially demonstrated the selectivity of prepared N-graphene for ORR in presence of glucose and D-gluconic acid in pH-neutral media [17].…”
Section: Introductionmentioning
confidence: 77%